Odpowiedzi

2010-03-17T16:36:38+01:00
1. 4x+12=-8x-9
4x+8x=-12-9
12x=-21 |:12
x=-1,75
2. -12x+x-7=3x-11
-12x+x-3x=7-11
-14x=4 |:(-14)
x=-0,29
3. -6x+2=-5x+3
-6x+5x=-2+3
-x=1 |*(-1)
x=-1
4. 16y-15=12y+3
16y-12y=15+3
4y=18 |:4
y=4,5
5. 2(2x+3)=3(5x-2)
4x+6=15x-6
4x-15x=-6-6
-11x=-12 |:(-11)
x=1,(09)1
6. 2(6y-2)=3(2y-3)
12y-4=6y-9
12y-6y=4-9
6y=-5 |:6
y=-0,8(3)
7. 5(x-7)=3(x-2)-1
5x-35=3x-6-1
5x-3x=35-6-1
2x=28 |:2
x=14
8.x-(x+2)=3+(x+1)
x-x-2=3+x+1
x-x-x=2+3+1
-x=6 |*(-1)
x=-6


Najlepsza Odpowiedź!
2010-03-17T16:38:21+01:00
4x + 12= -8x - 9
21=-12X /-12
X=7/4

-12x + x - 7= 3x -11
-14X=-4 /-4
X=3 1/2

-6x + 2= -5x + 3
-x=1
x=-1

16y - 15= 12y + 3
4y=18
y=4 1/2


2(2x + 3)= 3 (5x - 2)
4x+6=15x-6
-11x=-12
x=12/11

2(6y - 2)= 3 (2y - 3)
12y-4=6y-9
6y=-5
y=-5/6

5(x - 7)= 3 ( x - 2)-1
5x-35=3x-6-1
2x=28
x=14

x-(x+2)=3+(x+1)
x-x-2=3+x+1
-x=6
x=-6